Earnings management of Chinese central state-owned enterprises – the effects of state level incentives. Issue 6 (2nd November 2019) - Fan, Hong; Song, Xiaofei
Abstract: This study builds upon the argument of alignment effect and posits that the close alignment of the interests between Chinese central state-owned enterprises (CSOEs) and those of the Chinese central government creates state-level incentives (e.g. GDP volatility mitigation) for CSOEs to manage earnings. Consistent with our proposition we find that Chinese CSOEs engage in earnings management to reduce GDP volatility. Furthermore, we find that Chinese CSOEs only use the real earnings management approaches that also reduce enterprise earnings volatility to mitigate GDP volatility.